2010
DOI: 10.2460/javma.237.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of persistent pneumothorax by use of blood pleurodesis in a dog after surgical correction of a diaphragmatic hernia

Abstract: Case Description—A 15-kg (33-lb) pregnant female mixed-breed dog of unknown age was referred because of a 10-day history of difficulty breathing. Clinical Findings—Physical examination findings were dyspnea, tachypnea, decreased bronchovesicular sounds (bilateral), muffled heart sounds, and abdominal distention with palpable fetuses. Hematologic abnormalities included anemia, leukocytosis, and thrombocytosis. Abnormalities detected during serum biochemical analysis included decreases in concentrations of album… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…A review of pneumothorax by Pawloski et al 15 concluded that ABP should be the gold standard of postoperative care in human patients. In canine patients, blood pleurodesis has been reported effective for correction of pneumothorax following surgical correction of a traumatic diaphragmatic hernia, as well as spontaneous and persistent pneumothorax of multiple etiologies 19–21 . To the author's knowledge, this is the first reported use of ABP in veterinary patients for complications following lung lobectomy.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…A review of pneumothorax by Pawloski et al 15 concluded that ABP should be the gold standard of postoperative care in human patients. In canine patients, blood pleurodesis has been reported effective for correction of pneumothorax following surgical correction of a traumatic diaphragmatic hernia, as well as spontaneous and persistent pneumothorax of multiple etiologies 19–21 . To the author's knowledge, this is the first reported use of ABP in veterinary patients for complications following lung lobectomy.…”
Section: Discussionmentioning
confidence: 89%
“…The amount of intrapleural instilled autologous blood is between 5 and 10 ml/kg when the technique has been previously described in dogs, and the use of the ABP terminology is consistent with previous reports in the veterinary literature. 19 , 20 , 21 However, intrapleural instillation of autologous blood may be a more physiologically accurate term.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment options for management of pneumothorax associated with ruptured bullae or blebs include conservative management with placement of a thoracostomy tube and repeated thoracocentesis or continuous suction, blood patch pleurodesis, or surgical thoracotomy for identification and removal of the lung lobe from which air leakage has occurred. 1 , 18 , 31 , 32 Conservative management with repeated or continuous suction was not elected in this case because of the rapid recurrence of pneumothorax after drainage of the thoracotomy tube, the low reported success rate of conservative management 1 and because of concerns that repeated thoracocentesis or continuous suction could cause some of the other bullae or blebs to rupture. Blood patch pleurodesis was elected as an initial treatment option over thoracotomy in this case because of the fact that multiple blebs and bullae were present, which may have complicated identification of the ruptured bleb or bulla intraoperatively.…”
Section: Discussionmentioning
confidence: 99%